Finding myself as a cervical cancer survivor: A qualitative study. (August 2019) - Ochoa, Elizabeth; Carrillo, Gloria M.; Sanabria, Daniel
Abstract: Purpose: To determine the process and meaning of the experience of women with cervical cancer who had completed treatment within less than 5 years. Methods: Qualitative study that included 13 women with cervical cancer, who participated after receiving a year of treatment. The data was collected by conducting 16 in-depth interviews that took place in participants' domiciles. Grounded theory procedures were used to conduct the analysis. Results: "Finding myself as a cervical cancer survivor" was identified as the central dimension on the present study, confirmed by 5 subcategories: entering an unknown path, facing what no one can imagine, living with the disease, moving on regardless of the tiredness, and stop suffering for a new opportunity. Conclusion: Gaining an understanding of the reality that women with cervical cancer face reveals their strength and capacity to deal with difficulties and late side effects that need to be recognized by health professionals in the face of a disease categorized as deadly and dangerous. Highlights: This study is a referent in Colombia to approach the experience of patients with cervix cancer. It's importance of building awareness in the health team about the burden experienced by women with cervical cancer after a treatment. The identification of the experience allows developing interventions in nursing practice that improve the performance level of these patients.